Investigation and analysis of vascular accesses in elderly maintenance hemodialysis patients in Wuhan area in 2018 - FEI Shi-zhi; XIONG Fei; LI Hong-bing; WU Ai-chun (Linchuang shenzangbing zazhi)
Objective To analyze the vascular accesses of elderly maintenance hemodialysis(MHD) patients in Wuhan in 2018.Methods A total of 2 166 elderly MHD patients at age ≥60 from 44 hemodialysis units in Wuhan area in 2018 were enrolled as the elderly group,and another 1 844 MHD patients at age < 60 as the non-elderly group.The distributions of vascular accesses,were compared between the two groups.Stratified analysis was performed for the distribution of vascular accesses in patients with different sex,age and dialysis age in the elderly group.Results In the distribution of vascular accesses in elderly MHD patients in Wuhan,autogenous arteriovenous fistula(AVF) accounted for 69.11%,transplantation fistula for 0.65%,and tunneled cuffed catheter(TCC) for 26.36%,non-tunneled and non-cuffed catheter for 3.83%.The differences of AVF and TCC proportions in vascular access composition between the elderly group and the non-elderly group had statistical significance(P<0.01).In elderly MHD patients,the differences of AVF and TCC proportions in vascular access composition between males and females had statistical significance(P<0.01).The AVF proportions were negatively correlated with patient ages(P<0.01),and the TCC proportions were positively correlated with patients ages(P<0.01).The differences of transplantation fistula and non-tunneled and non-cuffed catheter proportions between patients with different sexes,ages and dialysis ages were none of statistical significance(P>0.05).Conclusions The composition of vascular accesses in elderly MHD patients in Wuhan is not ideal,and the level of vascular access surgery is relatively weak,has not achieved the goal recommended of the vascular access for hemodialysis in China,recommended through expert consensus.Efforts should be made to improve the level of vascular access surgery and establish a high-level,multidisciplinary cooperation vascular access team to improve the vascular access conditions in elderly MHD patients in Wuhan.